(untitled) (International Journal of Engineering and Computer Science, 2016)
Cloud Computing is process of hosting remote services over the internet. It provides data recovery easily .The system is having a persistent local backup which checks out periodically changes of data in the user folder. The compression technique is also the main objective of the system as to reduce the bandwidth which it takes for storing and accessing data from the cloud. The local backup process which is in the system itself where all the data of the user is stored securely. Video files are compressed automatically by the software known as FFMPEG and new copy of video file with compression is stored in to the local backup. The storage is over the cloud in the Microsoft one drive which has to be activated before storing data and retrieving data. The user data is updated each time and data backup is also present for the files added, deleted or modified. The one drive where the data is stored and accessible anytime and anywhere across the world. The user of data is the only authorized person to access the data. The sharing of data is possible and also the graph of various compressed and uncompressed file can be analyzed for the purpose of saving bandwidth. Data is protected both in local backup and stored over the cloud for automatically retrieving it. The result provides that the data security is given by maintaining two backups through which data can be easily retrieved with compressing videos to save the bandwidth